2009
DOI: 10.1192/bjp.bp.109.063529
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to depression in Sri Lanka

Abstract: BackgroundSusceptibility to depression results from genetic and non-familially shared environmental influences in high-income, Western countries. Environments may play a different role for populations in different contexts.AimsTo examine heritability of depression in the first large, population-based twin study in a low-income country.MethodLifetime depression and a broader measure of depression susceptibility (D-probe) were assessed in 3908 adult twins in Sri Lanka (the CoTASS study).ResultsThere were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 32 publications
7
24
1
Order By: Relevance
“…Overall, a very similar pattern of heritability has been shown in the current sample compared with results from twin studies in western countries for depression, fatigue, and tobacco use (Ball et al, 2009(Ball et al, , 2010cZavos et al, 2012). However, some differences were noted.…”
Section: Heritability Of Common Mental Disorderssupporting
confidence: 84%
“…Overall, a very similar pattern of heritability has been shown in the current sample compared with results from twin studies in western countries for depression, fatigue, and tobacco use (Ball et al, 2009(Ball et al, , 2010cZavos et al, 2012). However, some differences were noted.…”
Section: Heritability Of Common Mental Disorderssupporting
confidence: 84%
“…Finally, we ran a bivariate model to decompose the covariation between abnormal fatigue and D-probe (see Table 5 for parameter estimates). As a result of previously identified gender differences in D-probe, 28 we did not attempt to equate the model across A, additive genetics; C, environmental influences shared across twins; E, non-shared environments; AIC, Akaike's information criterion. a.…”
Section: Bivariate Twin Modelmentioning
confidence: 99%
“…Studying and comparing common disorders in low- to middle-income countries of non-Caucasian ancestry is crucial to test if findings derived from Western populations are truly generalisable. A study of depression in a large Sri Lankan sample of twins from the Colombo Twin and Singleton Follow-up Study (COTASS-2) [18] found a pervasive effect of the environment on individual differences in depression in men and stronger genetic effects in women, suggesting substantial differences in the aetiology of depressive symptoms in this population [19]. This study highlighted the importance of cross-cultural comparisons; because the environmental exposures associated with EOE and depression are likely to be specific to the cultural, economic and cultural context of the specific samples studied.…”
Section: Introductionmentioning
confidence: 99%